The Representation of The Ecological Crisis in Indonesian Novels: How Does The Social-Ecological System Occur? - Abimubarok, Achmad; Hikmat, Ade; Solihati, Nani (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. While Indonesian novels have been explored for their depiction of ecological crises, there has yet to be a detailed examination of how these narratives reflect the ensuing socio-ecological systems. This study investigates the portrayal of socio-ecological systems within Indonesian novels in the context of ecological crises. Employing qualitative methods and content analysis, this research utilizes the updated socio-ecological systems framework proposed by McGinnis and Ostrom (2014). The findings reveal various aspects of the crises represented, including forest destruction, forest fires, air pollution, animal extinction, and the degradation of natural reserves. Furthermore, the ecological crisis that has occurred actually gives rise to a socio-ecological system that represents the internal relationships among the resource system, government system, resource unit, and actors, and is influenced by external factors such as the social, economic, and political settings, and related ecosystems. Additionally, this representation of the socio-ecological system provides insights into the conditions of the ecological crisis in Indonesia, particularly in palm oil plantations and nature reserves.Keywords: Ecological Crisis, Social-Ecological System, Indonesian Novels, Ecocriticism